Dispersion modeling of solid core photonic crystal fiber - Yeo, Kwok Shien; Chow, Desmond M.; Tee, Din Chai; Wong, Wei Ru; Sandoghchi, Seyed Reza; Mahdi, Mohd Adzir; Mahamd Adikan, Faisal Rafiq (IEEE, 2012)
In this paper we calculate the dispersion values of our home-made solid core photonic crystal fiber (PCF) based on step index fiber model. Material dispersion and waveguide dispersion is taken into account while carrying out the calculation. The dispersion values predicted by this model agree well with that obtained by a commercial finite element method (FEM) solver.